Associations between cardiovascular-kidney-metabolic syndrome and disability in activities of daily living: a nationwide longitudinal study among the middle-aged and older adults in China - Zhang, Junfeng; Huang, Huijie; Lin, Zhan; Dong, Jingran; Zhang, Xiaoyan; Gao, Jing; Liu, Yin; Li, Changping; Cui, Zhuang (Frontiers in Public Health, 2025)
BackgroundActivities in daily living (ADLs) disability triggered by aging population and chronic diseases in the middle-aged and older adults has become a major public health challenge. Cardiovascular-kidney-metabolic (CKM) syndrome, as a combination of several chronic conditions, has not yet been studied to explore its association with ADLs disability. We examined the association between CKM syndrome and ADLs disability among middle-aged and older adults in China and whether it varied by age and socioeconomic status.MethodsParticipants were from China Health and Retirement Longitudinal Study (CHARLS), which conducted four waves of surveys from 2011 to 2018. CKM stage was calculated through disease and physical examination data from CHARLS database. Meanwhile, the degree of disability was assessed through the ADL scale. Generalized linear mixed model was used to perform multivariate analysis to explore the association between CKM syndrome and the risk of ADLs disability.ResultsThe proportion of CKM stage 0, 1, 2, and 3 among the 5,898 eligible participants (median age 60 years, 60.27% women) in 2011 were 14.70, 30.23, 41.39, and 13.68%. The risk of ADL disability was increased by 16% (odds ratio [95% confidence interval]; 1.16 [1.00–1.33]) and 33% (1.33 [1.12–1.58]) in CKM stages 2 and 3 compared with stage 0. In addition, there was a greater risk of BADL disability in 75+ age group compared to other age groups, but no significant association with IADL disability. In the subgroup aged 75+, the risk of BADL disability was increased for CKM stage 2/3 (1.48 [1.01–2.18]/1.67 [1.06–2.64]) compared with stage 0. Only in the lowest quartile of socioeconomic status group CKM stage rise was strongly associated with the risk of disability. The risk of ADL disability was greater for CKM stage 2/3 (1.45 [1.15–1.83]/1.48 [1.11–1.98]) compared to CKM stage 0 in the lowest economic status quartile.ConclusionFor middle-aged and older adults in China, CKM syndrome is a key risk factor for ADLs disability. Therefore, effective measures should be taken to manage CKM stage at the lowest possible level, especially in older and economically disadvantaged populations.